1988
DOI: 10.1111/j.1469-7610.1988.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Parents of Autistic Children: A Controlled Study

Abstract: Parents of 21 autistic children and of 21 children with other handicaps, matched for sex, age, IQ and father's occupation, were interviewed with a schedule known to discriminate between schizoid and non-schizoid people. Ratings were reliable and the interviewers remained "blind". Parents of autistic children, especially fathers, were significantly more often rated as having schizoid traits. They were also more intellectual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
61
1
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 21 publications
11
61
1
3
Order By: Relevance
“…In several studies, rates of 10-45% of social impairment, aloofness, shyness and pragmatic language impairment were present in fathers and mothers of children with autism or AS. [106][107][108][109][110][111][112][113][114] This finding did not differ in parents of children with autism with and without a history of language regression. 115 Regarding obsessive-compulsive behaviours in parents of multiplex autism families, a strong correlation of the severity of restricted repetitive and stereotyped patterns of behaviour, interests and activities in the child and rates of obsessive-compulsive traits or disorders were found in parents.…”
Section: Family Studiesmentioning
confidence: 86%
“…In several studies, rates of 10-45% of social impairment, aloofness, shyness and pragmatic language impairment were present in fathers and mothers of children with autism or AS. [106][107][108][109][110][111][112][113][114] This finding did not differ in parents of children with autism with and without a history of language regression. 115 Regarding obsessive-compulsive behaviours in parents of multiplex autism families, a strong correlation of the severity of restricted repetitive and stereotyped patterns of behaviour, interests and activities in the child and rates of obsessive-compulsive traits or disorders were found in parents.…”
Section: Family Studiesmentioning
confidence: 86%
“…For example, elevated difficulties in social skills in parents and siblings of children with an ASD are commonly found relative to parents and siblings of children with other developmental conditions, such as Down syndrome, while controlling for the stressor of a high-needs child in the home (Adolphs, Spezio, Parlier, & Piven, 2008;Bolton et al, 1994;Duchaine & Nakayama, 2006;Gillberg, 1989;Losh et al, 2009;Narayan, Moyes, & Wolff, 1990;Wolff et al, 1988). The presence of traits associated with ASD in parents and/or siblings has also been found to correlate with the severity of ASD in the child (Maxwell, ParishMorris, & Hsin, 2013;Sasson, Lam, Parlier, Daniels, & Piven, 2013;Szatmari et al, 2008;Wilson, Freeman, Brock, Burton, & Palermo, 2010).…”
Section: What Is the Broader Autism Phenotype?mentioning
confidence: 99%
“…Subsequent reports of ASD echoed Kanner's accounts of these shared characteristics in family members (Creak & Ini, 1960;Eisenberg, 1957;Gillberg, 1989;Piven et al, 1994;Wolff, Narayan, & Moyes, 1988). In the era of Harlow's studies of social deprivation in monkeys (e.g., Harlow & Harlow, 1962) and Bowlby's research on mother-child attachment (e.g., Bowlby, 1958), the presence of these shared characteristics was misinterpreted as evidence of a possible environmental cause.…”
mentioning
confidence: 99%
“…As early as 1957, clinical and experimental studies have demonstrated sub-clinical autistic symptomatology in family members of affected individuals [Eisenberg, 1957], including executive dysfunction (see below) in parents [Hughes et al, 1997] and siblings [Hughes et al, 1999] of children with autism, and social impairments in parents of affected children [Wolff et al, 1988]. Parents of affected children exhibit subtle language and communicative differences [Landa et al, 1991; and experience higher rates of major depressive disorder (19%) and social phobia [15%; Piven and Palmer, 1999].…”
mentioning
confidence: 98%